Case report: successful response to bevacizumab combined with erlotinib for a novel FH gene mutation hereditary leiomyoma and renal cell carcinoma - Bai, Xiaoming; Xiang, Dan; Huang, Mengxi; Chen, Yitian (Frontiers in Pharmacology, 2024)
FH-deficient Renal Cell Carcinoma (FH-deficient RCC) are inherited tumors caused by mutations in the fumarate hydratase (FH) gene, which plays a role in the tricarboxylic acid cycle. These mutations often result in aggressive forms of renal cell carcinoma (RCC) and other tumors. Here, we present a case of FH-deficient RCC in a 43-year-old woman with a history of uterine fibroids. She exhibited a new heterozygous mutation in exon six of the FH gene (c.799_803del, c.781_796del). The patient had multiple bone metastases and small subcutaneous nodules in various areas such as the shoulders, back, and buttocks. Biopsy of a subcutaneous nodule on the right side revealed positive expression of 2-succinate-cysteine (2SC), and FH staining indicated FH expression deletion. The patient underwent treatment with a combination of erlotinib and bevacizumab, which resulted in significant efficacy with moderate side effects. This treatment combination may be recommended as a standard regimen. This case underscores the importance of genetic testing in patients with advanced renal cancer to enhance diagnostic accuracy. Furthermore, it provides insights into potential treatment approaches for FH-deficient RCC.